Ibrutinib does not have clinically relevant interactions with oral contraceptives or substrates of CYP3A and CYP2B6. Issue 5 (18th September 2020) - de Jong, Jan; Mitselos, Anna; Jurczak, Wojciech; Cordoba, Raul; Panizo, Carlos; Wrobel, Tomasz; Dlugosz‐Danecka, Monika; Jiao, James; Sukbuntherng, Juthamas; Ouellet, Daniele; Hellemans, Peter
Abstract: Ibrutinib may inhibit intestinal CYP3A4 and induce CYP2B6 and/or CYP3A. Secondary to potential induction, ibrutinib may reduce the exposure and effectiveness of oral contraceptives (OCs). This phase I study evaluated the effect of ibrutinib on the pharmacokinetics of the CYP2B6 substrate bupropion, CYP3A substrate midazolam, and OCs ethinylestradiol (EE) and levonorgestrel (LN). Female patients (N = 22) with B‐cell malignancies received single doses of EE/LN (30/150 μg) and bupropion/midazolam (75/2 mg) during a pretreatment phase on days 1 and 3, respectively (before starting ibrutinib on day 8), and again after ibrutinib 560 mg/day for ≥ 2 weeks. Intestinal CYP3A inhibition was assessed on day 8 (single‐dose ibrutinib plus single‐dose midazolam). Systemic induction was assessed at steady‐state on days 22 (EE/LN plus ibrutinib) and 24 (bupropion/midazolam plus ibrutinib). The geometric mean ratios (GMRs; test/reference) for maximum plasma concentration (Cmax ) and area under the plasma concentration‐time curve (AUC) were derived using linear mixed‐effects models (90% confidence interval within 80%‐125% indicated no interaction). On day 8, the GMR for midazolam exposure with ibrutinib coadministration was ≤ 20% lower than the reference, indicating lack of intestinal CYP3A4 inhibition. At ibrutinib steady‐state, the Cmax and AUC of EE were 33% higher than the reference, which was not considered clinically relevant. No substantial changes were noted for LN, midazolam, or bupropion. No unexpected safety findings were observed. A single dose of ibrutinib did not inhibit intestinal CYP3A4, and repeated administration did not induce CYP3A4/2B6, as assessed using EE, LN, midazolam, and bupropion.